Primary pulmonary hyalinizing clear cell carcinoma with fusions of both EWSR1::CREM and IRF2::NTRK3: report of a case with an aggressive behavior - Wu, You-Li; Wu, Feng; Cao, Mian-Fu; Lan, Yang; Du, Ming-Shan; Yu, Song-Tao; Wang, Yan; Yan, Xiao-Chu; Bian, Xiu-Wu; Duan, Guang-Jie (Frontiers in Oncology, 2023)
Primary pulmonary hyalinizing clear cell carcinoma (HCCC) is a rare salivary gland-type tumor newly recognized in recent years, with approximately 21 cases reported to date in the English literature, which constitutes a challenge in pathology diagnosis, particularly in small biopsy specimens. Here, we present a case of pulmonary HCCC diagnosed by computed tomography-guided percutaneous lung biopsy in a 70-year-old man's right lower lung. Although the morphology and immunophenotype of the tumor suggested the diagnosis of mucoepidermoid carcinoma, fluorescence in situ hybridization failed to reveal the rearrangement of MAML2 gene, which is characteristic of mucoepidermoid carcinoma. Instead, further molecular genetic testing showed that the tumor harbored a rare EWSR1::CREM fusion combined with a previously unreported IRF2::NTRK3 fusion. Pulmonary HCCC is commonly regarded as a low-grade malignant tumor with an indolent course, but this case has a different biological behavior, presenting extensive dissemination and metastases at the time of diagnosis, which expands our understanding of the prognosis of this tumor. The patient has had five cycles of combination chemotherapy and has been alive with the tumor for eight months.